Mechanism of TNF- α inducing apoptosis and autophagy of chondrocytes by activating NF- κ B signal pathway: TNF-α inducing apoptosis and autophagy of chondrocytes - Liu, Muzi; Gong, Shiguo; Sheng, Xin; Zhang, Zihong; Yang, Jiaquan (Cellular and Molecular Biology, 2023)
This study aimed to explore the mechanism of apoptosis and autophagy of chondrocytes induced by tumor necrosis factor α (TNA-α) by activating the NF-κB signal pathway. For this purpose, 24 SD rats were selected for feeding. The knee cartilage was cut by ophthalmology and the chondrocytes were extracted. The chondrocytes were randomly divided into a control group (CG) and an observation group (OG). TNF-α of 50ng/mL was added before the beginning of the study, while the control group did not receive any treatment. The levels of IL-1, IL-6, IL-12, autophagy markers (Atg5, Atg7, LC3II/I), apoptosis-related indexes (Bax, Bcl-2), NF-κB signal pathway-related indexes (p-p65, p65, IκBα) protein expression, mRNA expression and apoptosis rate in chondrocytes were compared in each group. Results showed that the levels of IL-1, IL-6 and IL-12 in the OG were raised than those in the CG. The expression levels of autophagy markers Atg5, Atg7, LC3II/I and mRNA in the OG were reduced than those in the CG. The apoptosis rate and the expression of BaxmRNA and protein in the OG were higher than those in the CG, while the expression of Bcl-2mRNA and protein were lower than those in the CG. The p-p65, p65, IκBα protein and mRNA related to NF-κB signal pathway in the OG were raised than those in the CG. In conclusion, TNF-α can induce apoptosis and autophagy of chondrocytes by activating the NF-κB signal pathway.